2017
DOI: 10.1364/oe.25.010214
|View full text |Cite
|
Sign up to set email alerts
|

Direct laser printing of chiral plasmonic nanojets by vortex beams

Abstract: Donut-shaped laser radiation, carrying orbital angular momentum, namely optical vortex, recently was shown to provide vectorial mass transfer, twisting transiently molten material and producing chiral micro-scale structures on surfaces of different bulk materials upon their resolidification. In this paper, we show for the first time that nanosecond laser vortices can produce chiral nanoneedles (nanojets) of variable size on thin films of such plasmonic materials, as silver and gold films, covering thermally in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…Top views of b) left‐handed and c) right‐handed Ag nanojets. Reproduced with permission . Copyright 2017, The Optical Society.…”
Section: Helical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Top views of b) left‐handed and c) right‐handed Ag nanojets. Reproduced with permission . Copyright 2017, The Optical Society.…”
Section: Helical Structuresmentioning
confidence: 99%
“…In this area of original physical demonstrations, recent studies have shown that irradiation by such an OAM field can twist materials, such as metal, silicon, azo‐polymer, and even a liquid‐phase resin with the help of spin angular momentum (SAM) of circularly polarized light with the rotating electric field. This can thus shape helical nano/microstructures …”
Section: Introductionmentioning
confidence: 99%
“…Comparing to the results obtained for the first-order ( =1) OV generated with the s-waveplate [14], the demonstrated chiral nanoneedles also can be characterized by a ultra-sharp tips with a curvature radius down to 10 nm, while a height-to-width ratio, being a main geometric parameter of the structure, can be tuned via a size of the molten pool (or lens NA) and the film thickness, following the previously reported tendency [14]. For the twisted nanoneedles produced with the OV beams on the surface of transition metals, the underlying mechanism was attributed to either the OAM transfer to the transiently molten material [12] or the appearance of the characteristic spiral-shape intensity (temperature) pattern resulted from the interference of the incident donut-shape vortex beam with its reflected and distorted replica [14]. Taking into account that the spiral-shape beam used in this study has neither OAM nor SAM, the temperature-gradient driven capillary chiral mass transfer provides an alternative fabrication path, comparing to the radiation force action [12].…”
mentioning
confidence: 89%
“…Twisted mass transport enabled by the angular momentum of light (s ¼ AE1), associated with the rotating electric field present in circularly polarized light. [16][17][18][19][20][21][22] A total AM, [J ¼ ðl þ sÞ, of light refers to the sum of both the orbital and spin AM associated with both the beam's helical wavefront and polarization. [23][24][25] This total AM has been experimentally observed in studies of optically trapped microparticles exhibiting orbital and spinning motion depending on the orbital and spin AM of the trapping beam.…”
mentioning
confidence: 99%
“…[23][24][25] This total AM has been experimentally observed in studies of optically trapped microparticles exhibiting orbital and spinning motion depending on the orbital and spin AM of the trapping beam. [26][27][28] Separately, a pulsed orbital AM field has enabled the formation of nano-/microscale "twisted" needle-like structures (so-called twisted needles) on the surface of irradiated bulk tantalum (Ta), silicon (Si), copper (Cu) and silver (Ag), and gold (Au) thin films [16][17][18][19][20][21][22]29,30 (Fig. 1).…”
mentioning
confidence: 99%